2018
DOI: 10.1038/s41386-018-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychopharmacology of JNJ-55308942: evaluation of a clinical candidate targeting P2X7 ion channels in animal models of neuroinflammation and anhedonia

Abstract: Emerging data continues to point towards a relationship between neuroinflammation and neuropsychiatric disorders. ATP-induced activation of P2X7 results in IL-1β release causing neuroinflammation and microglial activation. This study describes the in-vitro and in-vivo neuropharmacology of a novel brain-penetrant P2X7 antagonist, JNJ-55308942, currently in clinical development. JNJ-55308942 is a high-affinity, selective, brain-penetrant (brain/plasma of 1) P2X7 functional antagonist. In human blood and in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 46 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…In our study, the expressions of P2X7R were augmented in hippocampus and mPFC, which was partly consistent with previous findings (Pan et al, 2014 ). In several very recently published articles, researchers showed that P2X7 receptor antagonists including JNJ-55308942 and brilliant blue G (BBG) could modulate neuroinflammation and anhedonia in rodent models (Bhattacharya et al, 2018 ; Farooq et al, 2018 ). Concerned that Apolloni et al ( 2016b ) demonstrated that clemastine inhibited the increase of P2X7R expression in SOD1 G93A mice in lumbar spinal cord compared to vehicle group, we applied clemastine, a safe and effective clinical drug, as a potential P2X7 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the expressions of P2X7R were augmented in hippocampus and mPFC, which was partly consistent with previous findings (Pan et al, 2014 ). In several very recently published articles, researchers showed that P2X7 receptor antagonists including JNJ-55308942 and brilliant blue G (BBG) could modulate neuroinflammation and anhedonia in rodent models (Bhattacharya et al, 2018 ; Farooq et al, 2018 ). Concerned that Apolloni et al ( 2016b ) demonstrated that clemastine inhibited the increase of P2X7R expression in SOD1 G93A mice in lumbar spinal cord compared to vehicle group, we applied clemastine, a safe and effective clinical drug, as a potential P2X7 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…P2X7 receptor activation induces K + efflux, which is needed for efficient NLRP3 inflammasome activation (Gustin et al, 2015). NLRP3 inflammasome trigger the activation of caspase-1, which causes the maturation of IL-1β and IL-18 and, consequently, increasing proinflammatory cytokine release (Bernier, 2012;Jo et al, 2016;He et al, 2017;Bhattacharya et al, 2018). This signaling appears to be in functional in microglia and not astrocytes (Gustin et al, 2015).…”
Section: P2x7 Receptor In Neuroinflammationmentioning
confidence: 99%
“…Similarly to the LPS-induced effects, P2X7 receptor overexpression was sufficient to trigger microglial activation in primary microglia derived from hippocampus ( Monif et al, 2009 ). Interestingly, a recent study evidenced that the selective P2X7 receptor antagonist, JNJ-55308942, inhibited neuroinflammation development induced in different rodent models by LPS, BCG or chronic stress ( Bhattacharya et al, 2018 ). Recently, efforts were made to detect in vivo neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These are the brain penetrant benzamides GSK1482160, 196 JNJ-42253432, 197 JNJ-47965567, 198 triazoles JNJ-54232334 and JNJ-54140515, 199 JNJ-54166060, 200 JNJ-54173717, 201 JNJ-54175446, 202 and JNJ-55308942. 203 These molecules have demonstrated P2X 7 receptor antagonist activities in rodent and human. Three of these molecules, GSK1482160, JNJ-54175446, and JNJ-55308942, have already moved into clinical trials for evaluation of the disorders of CNS.…”
Section: P2x 7 Receptor and Functions In The Cnsmentioning
confidence: 99%